Sistem Informasi Geografis Manajemen Aset di PT. PLN (Persero) Area Pelayanan Jaringan Surakarta - Yudi Eko Windarto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2013)
Electricity is one of major needs for human, therefore it is important to manage Electricity’s network. As the party who responsible in managing electricity in Indonesia, PT. PLN (Persero) keeps increasing and developing its quality including its speed and services. The increasing number of assets that are scattered in many locations, it will be faced with difficulties in finding or providing accurate information on the number and value of assets owned by PT.PLN (Persero).Asset Management Geographic Information System is one of the tools that are used to analyze spatial data then combine it with tabular data so easier information is obtained. Geographic Information System can analyze spatial data and non-spatial data. Geographic Information System can be used by individuals, organizations, and for those who need information related to positioning.Asset Management Geographic Information System helps PT.PLN (Persero) to fasten the decision-making process from field datas that have been visualized in application system; to monitor assets owned by PT.PLN (Persero) scattered both urban and rural areas. This monitoring process includes monitor the location of substations, poles, and customers.